2011
DOI: 10.4236/nr.2011.23023
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose and Sucrose Osmolytes Accumulated by Algae as Potential Raw Material for Bioethanol

Abstract: Currently, obtaining sustainable fuels, such as biodiesel and bioethanol, from cheap and renewable materials is a challenge. In recent years, a new approach being developed consists of producing, sugars from algae by photosynthesis. Sugar accumulation can be increased under osmotic stress (osmoregulation). The aim of this study is to show the pro-duction of sugars from algae, isolated from natural sources, and the effect of osmotic stress on fermentable sugars ac-cumulation. Strain isolation, production of sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Trehalose, a multifunctional molecule composing two glucose residues, is much more than a simple storage compound [6] and is now considered as a potential feedstock for bioethanol production [3]. Trehalose has been identified in a wide number of organisms, and the concentration of this molecule was only considerably lower in algae [39].…”
Section: Metabolites Responsementioning
confidence: 99%
“…Trehalose, a multifunctional molecule composing two glucose residues, is much more than a simple storage compound [6] and is now considered as a potential feedstock for bioethanol production [3]. Trehalose has been identified in a wide number of organisms, and the concentration of this molecule was only considerably lower in algae [39].…”
Section: Metabolites Responsementioning
confidence: 99%
“…While sucrose was accumulated in Hr-Hm and Hr-Ha growing under high salinity, glycerol was synthesized in Hr-Ws. Several studies have demonstrated that the degree of halotolerance in algae is directly linked to the type of osmolyte that accumulates (Bremauntz et al 2011, and references within). In stenohaline algae, sucrose is more often accumulated in response to osmotic stress, while in euryhaline species, glycerol is more commonly synthesized to adapt to high external salinity (Reed et al 1984;Warr et al 1985;Reed 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were enriched with four culture media, according to the salinity of the site of their acquisition, BG11, BG11/saline (25 g/L) and Guillar F/2 media [12], in the culture conditions reported [1]. After replanting two times in liquid media, the algae that demonstrated the largest growth were planted in the solid culture media with 10% agar-agar.…”
Section: Isolation and Cultivationmentioning
confidence: 99%
“…To determine intracellular sugars, a modified Muller method was used for the extraction [1], followed by quantification through the Dubois method.…”
Section: Analysis Of Intra-and Extracellular Sugarsmentioning
confidence: 99%
See 1 more Smart Citation